Neomorphic DNA-binding enables tumor-specific therapeutic gene expression in fusion-addicted childhood sarcoma - Hölting, Tilman; Cidre-Aranaz, Florencia; Matzek, Dana; Popper, Bastian; Jacobi, Severin J.; Funk, Cornelius M.; Geyer, Florian H.; Li, Jing; Piseddu, Ignazio; Cadilha, Bruno L.; Ledderose, Stephan; Zwilling, Jennifer; et al. (Molecular cancer, 2022)
Chimeric fusion transcription factors are oncogenic hallmarks of several devastating cancer entities including pediatric sarcomas, such as Ewing sarcoma (EwS) and alveolar rhabdomyosarcoma (ARMS). Despite their exquisite specificity, these driver oncogenes have been considered largely undruggable due to their lack of enzymatic activity.